The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
53rd AIAA Aerospace Sciences Meeting 2015
DOI: 10.2514/6.2015-0674
|View full text |Cite
|
Sign up to set email alerts
|

Strain Effects in Partially Premixed Methane-air Jet Flames

Abstract: A large-eddy simulation (LES) subgrid combustion model has been developed based on an innovative application of the linear-eddy model to the counter flow configuration (LEM-CF). This subgrid model is developed by parameterizing flame statistics from the LEM-CF sub-model in terms of a reduced set of variables. A database of closure statistics for LES transport equations for these variables is then generated. The run-time application of the model within LES retrieves the closure statistics from the database resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…We have observed that bandwidths ranging between 0.005 and 0.05 for a Gaussian kernel function are enough to smoothly capture the important characteristics present in the experimental data. The joint KDE is 14 implemented in Python using the in-built functions available in their scikit-learn library [31]. These joint PDFs are constructed at each axial and radial location in the flame using the instantaneous pointwise measurements.…”
Section: Joint Pdf Construction Via Kdementioning
confidence: 99%
See 2 more Smart Citations
“…We have observed that bandwidths ranging between 0.005 and 0.05 for a Gaussian kernel function are enough to smoothly capture the important characteristics present in the experimental data. The joint KDE is 14 implemented in Python using the in-built functions available in their scikit-learn library [31]. These joint PDFs are constructed at each axial and radial location in the flame using the instantaneous pointwise measurements.…”
Section: Joint Pdf Construction Via Kdementioning
confidence: 99%
“…The two limits of a presumed PDF shape with a limited set of parameters and the solution for a PDF transport equation leave ample room in between for intermediate approaches, which may be based on the construction of PDFs based on simulation [11][12][13][14] or experimental data. For example, Goldin and Menon [11,12], Sankaran et al [13] and Calhoon et al [14] built joint scalar PDFs, which are parameterized by an appropriate set of lower moments using simulations based on the linear-eddy model (LEM) [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, these moment-based models tend to be more computationally efficient than more advanced models that seek to directly evaluate unclosed terms in the governing equations, such as the PDF transport approach [3], the LEM-LES [4] and the ODT-LES [5] approaches. The use of lowdimensional stochastic models, such as the linear-eddy model (LEM) [6] and the one-dimensional turbulence (ODT) model [7] to construct PDFs and conditional means also provide an a priori tabulation approach for both conditional statistics and PDFs [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%